Human-Centric Functional Modeling and Condensed Matter Physics - Williams, Andy; Haliki, Emir (My University, 2021)
The newly emerging sciences of Human-Centric Functional Modeling provides an approach towards modeling systems that is hypothesized to maximize human capacity to understand and navigate complexity in those systems. This paper provide an overview exploring how Human-Centric Functional Modeling might be applied in condensed matter physics, and how this increase in capacity to understand complexity might be achieved.
Keywords: condensed matter physics; Human-Centric Functional Modeling